Cryoablation: safety of same day discharge. (14th October 2021) - Carrington, M; Silverio Antonio, P; Nunes-Ferreira, A; Rodrigues, T; Cunha, N; Couto Pereira, S; Brito, J; Alves Da Silva, P; Valente Silva, B; Lima Da Silva, G; Carpinteiro, L; Cortez-Dias, N; et al.
Abstract: Introduction: Discharge after overnight hospital stay is standard procedure in patients submitted to elective atrial fibrillation (AF) ablation. Taking into consideration the low rate of cryoablation procedure complications could the same day discharge be an option? Purpose: To assess the safety of same day discharge of patients submitted to AF cryoablation. Methods: Single-center retrospective study of consecutive patients admitted to elective AF cryoablation in a tertiary center between February 2017 and November 2020. Patients were divided into two groups: same day discharge and next day discharge. Only patients submitted to ablation until 4 p.m. were included. Complication rates were obtained up to six months after the procedure. Complications were defined as death, pericardial tamponade, hematoma requiring evaluation and/or intervention, major bleeding requiring transfusion, hospital admission related to the procedure. Results: One hundred fifty-four patients were included, with a mean age of 61±10.9 years, 66.2% were males, 18.2% with diabetes, 65.6% with dyslipidemia, 77.9% with hypertension, 10.4% with chronic kidney disease KDIGO stage 3 or more. Median follow-up of 436 [178 – 729] days. Most of the patients had paroxysmal (73.4%) and persistent short duration AF (23.4%). Sixty-two patients (40.3%) were early discharged and there were no differences between the two groups regarding epidemiological and clinical characteristics (p=NS). A very low rate of complications in both groups was observed, occurring in 6.5% of patients with early discharge and in 8.7% of patients in overnight stay, without statistical significance between the two groups (p=0.61). The most frequent complications were local hematoma (5 patients, 2 in early discharged group), pericardial effusion (3 patients, all in overnight stay), femoral pseudo-aneurism (2 patients, 1 in each group) and arteriovenous fistula (1 patient in overnight stay group). The type of complications did not differ between the two groups (p=0.51). Two patients died during follow up, and this was unrelated to the procedure. In addition, no difference in success rate and arrhythmic recurrence was observed between the two groups (p=NS). Conclusion: Our study suggests that it is safe to early discharge patients submitted to AF ablation, reducing the hospital stay length in selected patients. Larger studies are needed to confirm this data before routine implementation of this strategy. Funding Acknowledgement: Type of funding sources: None.